List of commidities - Teasdale, John, businessman
Printed list of commodities with handwritten prices current in Charleston, [S.C.].
Businessman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Charleston (S.C.) -- Commerce; Businessmen